TRANSFORMASI TEKS SUTASOMA DARI KAKAWIN KE NOVEL - Zuriati Zuriati; Oom Rohmah Syamsuddin (Faculty of Humanities, Jember University, 2011)
Sutasoma novel composed by Cok Sawitri is based on Sutasoma Kakawin written by Mpu Tantular. Both writings, novel and kakawin (poem), form a different literature genre. The genre transformation from kakawin to novel indicates that Tantular’s Sutasoma finds its transformation in Sawitri’s Sutasoma. Based on this, this article aims at elaborating the transformed elements in the two writings and discussing whether the transformation also has changed the textual stuctures (story), messages, functions. Structural analysis to the texts shows that the transformation has happened to the protagonist, Jayantaka, forming a transformation from Sutasoma and conversely, Sutasoma forms a transformation from Jayantaka. Novel seems to have voiced freedom in choosing faith, whereas kakawin voices the only one best religion. The transformation, however, keep their textual structure and functions unchanged, i.e. life history and serving as a legitimacy for Budhism as the best religion, which during the Majapahit era had been seen as the second and inferior. Keywords: Sutasoma, kakawin, transformation, novel, structure